Universal Credit (Miscellaneous Amendments, Saving and Transitional Provision) Regulations 2018 (SI 2018/65)- Transition to UC Housing Payment : Report by the Social Security Advisory Committee under Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions accordance with Section 174(2) of that Act.: Report by the Social Security Advisory Committee under Section 174(1) of the Social Security Administration Act 1992 and statement by the Secretary of State for Work and Pensions accordance with Section 174(2) of that Act. (January 2018) - Great Britain., Social Security Advisory Committee,
No abstract available